Follow-up conditions of care and associated factors among adult hypertensive patients during COVID-19 at West Arsi public health facilities, Southeastern Ethiopia: A multi-center cross-sectional study - Hiko, Ahmed; Assefa, Nega; Ataro, Zerihun; Sertsu, Addisu; Yadeta, Elias; Balcha, Teganu; Amano, Abdulkerim; Asfaw, Henock; Dechasa, Deribe Bekele; Nigussie, Kabtamu; Abdisa, Lemesa (Frontiers in Public Health, 2022)
Abstract Objective: The purpose of this study was to assess follow-up conditions of care and its associated factors among adult hypertensive patients during COVID-19 in public health facilities of West Arsi, Southeastern Ethiopia Methods: A health facility-based retrospective cross-sectional study was conducted among 423 adult hypertensive patients in the West Arsi public health facilities from July 5 to August 6, 2021. A systematic random sampling technique was used to recruit the study participant. Data were collected through face-to-face interviews and reviewing medical records. Data were entered into Epidata version 3.1 before it was transferred to SPSS version 26 for analysis. Bivariable and multivariable logistic regression analysis were performed to identify factors associated with follow-up conditions of care. To declare a significant association, a 95% confidence interval and a p-value of 0.05 were used. Results: The magnitude of poor follow-up conditions of care during COVID-19 was 29% (95% confidence interval: 24.9%-33.4%), according to this study. Age≥ 60 years (adjusted odds ratio=3.55; 95% confidence interval:2.09- 6.03), transportation problem (adjusted odds ratio=2.43; 95% confidence interval:1.28-4.61), fear of COVID-19 (adjusted odds ratio=3.34; 95% confidence interval: 1.59-7.01), co-morbidity (adjusted odds ratio=1.93; 95% confidence interval: 1.14-3.26) and physical distancing (adjusted odds ratio=2.43; 95% confidence interval: 1.44-4.12) were significantly associated with poor follow-up conditions of care. Conclusions: In our study, 29% of the participants had poor follow-up care conditions. The poor follow-up condition of care was significantly associated with age, fear of COVID-19, transportation problems, comorbidity, and physical distancing. Therefore, more emphasis should be placed on the elderly, comorbid conditions, and identifying factors that limit patients' follow-up conditions of care. Keywords: Attendance, Follow-up, Hypertension, COVID-19, Associated factors, Ethiopia